Folder of army intelligence correspondence and memoranda regarding German and IRA activity in Ireland, - O'Donoghue, Florence, 1895-1967 (1942)
Includes a handmade Christmas card addressed to O'Donoghue as editor of 'An Cosantóir' and a list of Irishmen employed in Germany and other Irishmen who have come under special notice there.